Effect of heat and humidity on in situ rumen degradability of cottonseed - Estrada, A.; La O, Oreste; Portillo, J. J.; Herrera, Rafael Segundo; Castro, Beatr?z I.; Rios, F. G. (Cuban Journal of Agricultural Science, 2011)
An in situ experiment was performed in the rumen to determine the DM and organic matter degradability of cottonseed, both normal and treated with heat and humidity. Four adult male sheep were used and fitted with rumen cannula. The samples were incubated for 3, 6, 9, 12, 24, 48, and 72 h in ventral position in the rumen. The values of potential degradability (a+b) varied from 56.4 up to 57.5, and from 86.59 up to 81.00 % for DM and CP of normal and treated seed, respectively. However, the c fraction, for DM and for CP, had better performance in the normal seed, compared with the treated with heat and humidity. The dynamics of rumen degradation evidenced increasing trend, from the first to the last incubation time, with differences (P < 0.01) in the treated and non-treated seeds. The chemical composition had adequate concentrations in this feed, with values up to 23.12 and 22.94 %, for CP in non-treated and treated seed meal, respectively. It was concluded that by humidifying the seed, there is higher availability of CP and DM for the ruminant animals. Besides, there is an efficient and easy to use alternative in animal feeding, with important contribution of bypassing proteins for the different feeding systems. Further studies on metabolism and productive indicators are recommended to support these results. Key words: cottonseed, degradability, DM, protein.